2012
DOI: 10.1001/jama.2012.13088
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lynch Syndrome Among Patients With Colorectal Cancer

Abstract: Context Lynch syndrome is the most common form of hereditary colorectal cancer (CRC) and is caused by germline mutations in DNA mismatch repair (MMR) genes. Identification of gene carriers currently relies on germline analysis in patients with MMR-deficient tumors, but criteria to select individuals in whom tumor MMR testing should be performed are unclear. Objective To establish a highly sensitive and efficient strategy for the identification of MMR gene mutation carriers among CRC probands. Design, Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
394
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 465 publications
(413 citation statements)
references
References 36 publications
(78 reference statements)
10
394
3
6
Order By: Relevance
“…ing had been driven by the use of clinical guidelines based on age and family history, such as the Amsterdam (Vasen et al, 1991;Vasen et al, 1999) and Bethesda criteria (Rodriguez-Bigas et al, 1997;Umar et al, 2004). However, it has been shown that up to 50% of mutation carriers do not fulfill the Amsterdam criteria and 40-45% of families fulfilling Amsterdam criteria do not have MSI on tumor testing (Pino and Chung, 2011;Syngal et al, 2000) The Bethesda guidelines incorporate tumor histopathologic features and while more sensitive, can still miss 12-28% of LS cases (Canard et al, 2012;Hampel et al, 2008;Julie et al, 2008;Moreira et al, 2012b;van Lier et al, 2012). In 2009, the 'Jerusalem criteria' recommended IHC or MSI testing be carried out on all CRC, where the patient is under the age of 70 at diagnosis (Boland and Shike, 2010).…”
Section: Age and Clinical-based Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…ing had been driven by the use of clinical guidelines based on age and family history, such as the Amsterdam (Vasen et al, 1991;Vasen et al, 1999) and Bethesda criteria (Rodriguez-Bigas et al, 1997;Umar et al, 2004). However, it has been shown that up to 50% of mutation carriers do not fulfill the Amsterdam criteria and 40-45% of families fulfilling Amsterdam criteria do not have MSI on tumor testing (Pino and Chung, 2011;Syngal et al, 2000) The Bethesda guidelines incorporate tumor histopathologic features and while more sensitive, can still miss 12-28% of LS cases (Canard et al, 2012;Hampel et al, 2008;Julie et al, 2008;Moreira et al, 2012b;van Lier et al, 2012). In 2009, the 'Jerusalem criteria' recommended IHC or MSI testing be carried out on all CRC, where the patient is under the age of 70 at diagnosis (Boland and Shike, 2010).…”
Section: Age and Clinical-based Criteriamentioning
confidence: 99%
“…Despite this, it has long been established the presence of dMMR or MSI in rectal cancer is highly predictive of Lynch syndrome (≤75% cases) (de Rosa et al, 2016;Nilbert et al, 1999). Thus, whenever a dMMR rectal cancer is identified, confirmatory genetic testing should be pursued, either through direct genetic testing of MMR genes (Beamer et al, 2012;Dineen et al, 2015;Moreira et al, 2012a) or as part of a multiplex NGS gene panel (Yurgelun et al, 2015). Even after diagnosis, the optimal management of Lynch patients with rectal cancer remains controversial.…”
Section: Rectal Cancer With Msimentioning
confidence: 99%
“…2 Performance of clinical criteria was taken from a recent international study. 27 The family mutation test in relatives was assumed to have 100% sensitivity and specificity. 14 Disease epidemiology.…”
Section: Parametersmentioning
confidence: 99%
“…Clinical presentation, histopathologic features, genetic susceptibility, and recommendations for surveillance Registry data from Denmark, Finland, Italy, Australia, and from the Epicolon study suggest that 21-73% of the families that fulfil the AC1 and/or AC2 represent FCCTX 16,[26][27][28] (Figure 1). Age at onset shows considerable interfamily as well as intrafamily variability with colorectal cancer diagnosed at a higher mean age (mean 57.3 years) in FCCTX than in Lynch syndrome (mean 49.7 years; Figure 1).…”
mentioning
confidence: 99%